Health Care Workers' Challenges in the Care of a COVID-19 Patient. Issue 4 (October 2020) - Gordon, Ayla; Lyons, Caitlin; Rao, Sheldon; Finoli, Lauren
Abstract : The COVID-19 pandemic has introduced us to new challenges with personal protective equipment, long shifts, and changes in regular routines. This has placed a tremendous stress on health care workers. This article defines the various health care worker challenges, both at the bedside and on a personal front. Therapeutic strategies are discussed.